Identification and antibiotic resistance of Streptococcus agalactiae from red hybrid tilapia (Oreochromis niloticus) in local wet markets - Auzureen MZA; Ruhil Hayati Hamdan; Jamaludin, M. H. (2016)
The existence of ethiology disease like Streptococcus agalactiae could be major problems in aquaculture field. In this study, investigations of red tilapia sold around local wet market were recorded. To detect the S. agalactiae in wet markets from disease potential and measure the antibiotic susceptibility test. Selected organs such as eyes, gills, heart and intestine were inoculated onto blood agar and incubated at 37°C for 24 h. Morphology of S. agalactiae were Gram-positive, translucent pin point colony, and has oxidase and catalase negative. Eight isolates of S. agalactiae were confirmed using PCR. The isolates samples were susceptible to imipenem (10 µg), gentamicin (10 µg), ciprofloxacin (5 µg) and nalidixic acid (30 µg). In contrast, they were resistance to ampicillin (10 µg), amoxicillin-clavulanic (20/10 µg), erythromycin (5 µg), neomycin (30 µg), norflaxacin (10 µg), streptomycin (10 µg) and trimethoprim-sulphamethoxazole (1.25/23.5 µg). Furthermore, the occurrence of resistant isolates is a matter of public health concern.